2022
DOI: 10.1155/2022/5850899
|View full text |Cite
|
Sign up to set email alerts
|

Mining Important Herb Combinations of Traditional Chinese Medicine against Hypertension Based on the Symptom-Herb Network Combined with Network Pharmacology

Abstract: Although data mining methods are extensively used in the rule analysis of famous old traditional Chinese medicine (TCM) experts’ prescriptions for the treatment of hypertension, most of them only mine the association between herbs and herbs, ignoring the importance of symptoms in the disease. This study collected 439 cases of hypertension treated by famous old TCM experts from the FangNet platform. Using the structure network algorithm, the symptom-herb network was constructed, which redefined the importance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Studies have found that single-flavored traditional Chinese medicine, traditional Chinese medicine compounds, and traditional Chinese medicine extracts partially affect blood pressure, particularly in preventing damage to several target organs caused by hypertension. Traditional Chinese medicine in hypertension treatment involves multiple targets and pathways to lower blood pressure ( Sun et al, 2022 ). For example, 13 compounds are found in Puerariae Lobatae Radix.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that single-flavored traditional Chinese medicine, traditional Chinese medicine compounds, and traditional Chinese medicine extracts partially affect blood pressure, particularly in preventing damage to several target organs caused by hypertension. Traditional Chinese medicine in hypertension treatment involves multiple targets and pathways to lower blood pressure ( Sun et al, 2022 ). For example, 13 compounds are found in Puerariae Lobatae Radix.…”
Section: Introductionmentioning
confidence: 99%